Theoretical study of MgO(001) surfaces: Pure, doped with Fe, Ca, and Al, and with and without adsorbed water - Almeida, A. L.; Martins, JBL; Longo, Elson [UNESP]; Furtado, N. C.; Taft, C. A.; Sambrano, JR; Lester, W. A. (Wiley-Blackwell, 2001)
Ab initio calculations of large cluster models have been performed in order to study water adsorption at the five-fold coordinated adsorption site on pure Mg(001) and MgO(001) surfaces doped with Fe, Ca, and Al. The geometric parameters of the adsorbed water molecule have been optimized preparatory to analysis of binding energies, charge transfer, preferential sites of interaction, and bonding distances. We have used Mulliken population analysis methods in order to analyze charge distributions and the direction of charge transfer. We have also investigated energy gaps, HOMO energies, and SCF orbital energies as well as the acid-base properties of our cluster model. Numerical results are compared, where possible, with experiment and interpreted in the framework of various analytical models. (C) 2001 John Wiley & Sons, Inc.
Keywords: MgO; ab initio; water adsorption; Fe; Ca; Al; theoretical study